What are the perceptions of nurses working in child health regarding their role in child protection? : a mixed method study : Master of Philosophy in Nursing at Massey University, New Zealand - Shallard, Grace Ann (Massey University, 2019)
The global and national figures of child abuse and neglect are overwhelming and highlight an imminent need to focus on the well-being of tamariki1. Due to the long-lasting individual and societal impact of child abuse and neglect, it is a profoundly important health issue. Nurses are not only the largest group of health professionals, but they are typically at the forefront of health care and have a unique and significant ability not only to detect, but also to intervene in and prevent situations of child abuse and neglect. Despite their potential impact, they have rarely been the focus of investigation in this area, particularly in New Zealand. This thesis presents research undertaken to explore the current perceptions of nurses working in child health in regards to their role in child protection. A mixed method study was conducted using a sequential explanatory (two-phase) design. These distinct stages comprised of a survey and subsequent, complementary interviews. The quantitative aspect of the design was conducted through a survey; there were 134 surveys included in the analysis and these data were used to inform the second phase which comprised of six complementary interviews. This qualitative aspect of the design drew on grounded theory approaches. The main findings of this research can be divided into the following categories. Eyes and ears: nurses are regularly exposed to children who have experienced child abuse or neglect and are well positioned to detect abuse and neglect. Hands: Nurses engage in this sphere in a number of ways-including medically caring for children who have been abused or neglected, coordinating care, making referrals, and practically supporting in a wide variety of ways. Head: Despite most nurses having received training in this area, only half of nurses describe feeling confident to identify child maltreatment. Furthermore, although there are discrepancies in area, there is little standardisation of how nurses engage with this sphere. There are a number of both supports and barriers; the main barriers being lack of certainty and limited confidence in social services. Heart: Nurses experience deep and profound emotions when engaging in this sphere, which not only effects nurses personally, but also affects decision making and quality of care. Gut: Nurses rely on gut feelings to make decisions, an important and advanced way of knowing. Finally, it was clear, that nurses deeply care for the children they work with and the wellbeing of children is at the centre of all they do.
Keywords: Pediatric nursing; Child health services; Child welfare; New Zealand; Nurses; Attitudes